RECONSTRUCTING THE PROCESS OF FORMATION OF RURAL COMMUNITIES (ON THE EXAMPLE OF MACHADA VILLAGE) - Hapizov, Sahban Magomedovic; Tupcokova, Larisa Kazbekovna; Sehmagomedov, Magomed Gadzievic (History, Archeology and Ethnography of the Caucasus, 2020)
Based on the analysis of archeological material, written sources and oral tradition, the paper attempts to recreate the history of formation of Machada rural community in Nagorny Dagestan. According to a popular version in Dagestan historiography, Machada village was believed to be founded in the early 16th century. However, across the northern border of the village, on a large steep mountain slope, there is a burial with stone boxes belonging to the 6th – 8th centuries AD. Thus, the foundation of Machada settlement should be dated at least 6th century AD. At the same time, 1.5 km away from Machada, a medieval settlement of Choloda is located, whose inhabitants moved to Machada at the beginning of the 16th century. The inhabitants of the settlement located on the northern outskirts of Machada also moved there. Despite the emergence of the rural community in the first half of the 16th century, a new cemetery was founded there only from the 1630s. Thus, for about a century the inhabitants of Machada buried their dead in the Muslim cemetery of Choloda. Due to the large areas of farming lands around Machada, they were able to accept the newcomers. The largest resettlement presumably occurred in the 16th century from Khunzakh, which led to the formation of one of the four kindred groups of Machada. The other three tukhums were formed due to the resettlement of residents of neighboring tukhum settlements to Machada. At the end of the 16th century, the formation of a tukhum structure of 4 tukhums occurred – related groups, which began to accept the later settlers. Therefore, the use of retrospective method allows to give answers to the main questions, emerged before researchers of history of formation of rural communities in Nagorny Dagestan.